Flexural behavior of CFRP-aluminum fuselage frames with bolted splice joints. Issue 1 (1st September 2022) - He, Boling; Lu, Yuwei; Liu, Yupeng
Abstract: Few work concerned on the flexural strength of carbon fiber reinforced plastic (CFRP)-aluminum fuselage frames with bolted splice joints used in aeronautical industry. To provide help for the design of CFRP aircraft strcutures, this paper investigated the flexural behavior of CFRP-aluminum fuselage frames with bolted splice joints experimentally. Firstly, CFRP-aluminum fuselage frames were fabricated with mid-span bolted splice joints. The joints comprised: reinforced or unreinforced aluminum splice plates bolted to the fuselage frames. The bolt diameters were 4.76mm and 6.35mm. Then, the effects of splice plate and bolt dimeter on flexural behavior of CFRP-aluminum fuselage frames with bolted splice joints were investigated through four-point bending test. It has been shown that the introduction of reinforced splice plate improves the structural load capacity. However, increasing bolt diameter lowers the flexural strength of CFRP-aluminum fuselage frames with bolted splice joints. This splice jointed structure is a representative part of the rear fuselage, and the experimental results will be commonly instructive for the the aeronautical CFRP joining applications.